The Determinant Factors on Social Rehabilitation of Drug Abuse Victims - Elly Kuntjorowati (Jurnal Penelitian Kesejahteraan Sosial, 2015)
A large number of teenage drug abuse victims, count three million, out of Indonesian population, cause the government to issue law. The law No. 35, 2009 on drug abuse, states that victims of drug abuse shall undergo medical rehabilitation and social rehabilitation. The Ministry of Social Affairs as the competent institutions to implement social rehabilitation also issued minister regulation (Permensos) No. 26, 2012 on Standards of Social Rehabilitation of drug abuse victims. This research means to know the determinant factors in social rehabilitation of drug abuse victims, and to know the supporting and handycap factors on social rehabilitation of drug abuse victims. The result reveals that there is a number of83.33 percent respondents said that the determinant factors of social rehabilitation of drug abuse victims are the of urine test, sports and health care, character education, not committing a crime, and worship according to their own religion, understanding the theory and practice of motorcycles worksshop, cars and computers. Another factor that support is thegovernment policy on IPWL for NGO’s working in the field of social rehabilitation of drug abuse victims and regulation of social rehabilitation liability for drug abuse victims, and professional persons such as counselors and assistants. The handicap factor is the parent and neighborhood attitude toward drug abusers who are not willing to accept the ex-victimsreturning home. Bali Province does not have a government social rehabilitation center, so it should maximize NGO to implement social rehabilitation for victims of drug abuse.